The moon, the stars, and Madame Burova : a novel - Hogan, Ruth, 1961- (William Morrow, an imprint of HarperCollins Publishers, 2021)
After a lifetime of keeping other people's secrets, fortune teller Madam Burova, before she can have a little piece of life for herself, must fulfill a promise made in the 1970s, when she and her girlfriends were carefree, with their whole lives still before them.